2013
DOI: 10.1016/j.bbrc.2012.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Migfilin’s elimination from osteoarthritic chondrocytes further promotes the osteoarthritic phenotype via β-catenin upregulation

Abstract: Osteoarthritis (OA) is a debilitating disease of the joints characterized by cartilage degradation but to date there is no available pharmacological treatment to inhibit disease progression neither is there any available biomarker to predict its development. In the present study, we examined the expression level and possible involvement of novel cell-ECM adhesion-related molecules such as Iintegrin Linked Kinase (ILK), PINCH, parvin, Mig-2 and Migfilin in OA pathogenesis using primary human articular chondrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“… 38 Accordingly, in examined osteoarthritis patient samples, both the mRNA and protein expression of Migfilin were dramatically elevated and correlated with the development and progression of disease. 39 The findings showing positive expression of Migfilin in human leiomyosarcoma and osteoarthritis have been supported by similar statistical analyses of other human malignancies. Increased Migfilin expression can be detected in advanced glioma tissue samples and indicates a poor patient outcome.…”
Section: Migfilin and Cancer Developmentsupporting
confidence: 55%
“… 38 Accordingly, in examined osteoarthritis patient samples, both the mRNA and protein expression of Migfilin were dramatically elevated and correlated with the development and progression of disease. 39 The findings showing positive expression of Migfilin in human leiomyosarcoma and osteoarthritis have been supported by similar statistical analyses of other human malignancies. Increased Migfilin expression can be detected in advanced glioma tissue samples and indicates a poor patient outcome.…”
Section: Migfilin and Cancer Developmentsupporting
confidence: 55%
“…We also found that CEMIP modulated the Wnt/β-catenin signaling, a well-known regulator of EMT, in human chondrocytes. The Wnt/β-catenin pathway contributes to OA pathogenesis 43,44 . We previously observed that β-catenin accumulated along chondrocytes dedifferentiation leading to leptin production 17 .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these foci (61.5 %) were related to OA located within peripheral joints, spinal (zygapophyseal) joints and discs (discopathy) as shown by concomitant CT, which suggests involvement of integrin a v b 3 in OA. Structural changes in OA involve cartilage, fibrocartilaginous structures, synovium, subchondral bone and periarticular ligaments [36][37][38]. In response to mechanical or metabolic stress, the cartilage chondrocytes phenotype may change resembling to that of hypertrophic or dedifferentiated chondrocytes as obtained when primary chondrocytes are cultured in vitro, with a shift from anabolic to catabolic chondrocyte profile [38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%